6-9p+4p=

Simple and best practice solution for 6-9p+4p= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-9p+4p= equation:


Simplifying
6 + -9p + 4p = 0

Combine like terms: -9p + 4p = -5p
6 + -5p = 0

Solving
6 + -5p = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -5p = 0 + -6

Combine like terms: 6 + -6 = 0
0 + -5p = 0 + -6
-5p = 0 + -6

Combine like terms: 0 + -6 = -6
-5p = -6

Divide each side by '-5'.
p = 1.2

Simplifying
p = 1.2

See similar equations:

| -3(x-8)-5=9(x+2)11 | | 99=-m+8(8+m) | | a/6=6 | | 3z=90 | | y-(-8)=(6/7)(x-5) | | 3x/5-3x/5-7 | | -7.2=1.3n-0.3n-1.0 | | 5(2x+4)+3(2x-2)=24 | | x-.50x=43 | | (y+1)+1=3y | | f-g=3g | | 5(-8b-4)=180 | | 7-(-10+3x)=-238 | | y-(-3)=(8/9)(x-4) | | 2(2-2x)= | | 3x+7=x-21 | | 3x+29-2x+4=-4x | | 2000+9=1000 | | 12ab^2+4ab-16a^3b^2= | | 6(1+6x)=-102 | | -4(u+5)+3u= | | 10d-6=4s-15-3d | | 3(5-4a)=99 | | 6x+5+4x-3=122 | | -92=4(3k-2) | | 8x^2+2x+-15=0 | | z+.625=.9375 | | (x+5)2=108 | | (7+y)(4y+5)=0 | | 20+12x=-128 | | (m^5n^5)^1/6/3(mn)^-1/6 | | 3n=1/81 |

Equations solver categories